Valine in Broiler Diets: A review (The International Journal for Scientific Research, 2024)
Valine (Val) is the 4th limiting amino acid in a corn and soybean meal–based diet for broiler chicken, after methionine, lysine, and threonine. Valine, isoleucine, and leucine represent the branched-chain amino acids (BCAAs) family. It was reported that the performance of broilers is adversely affected by an imbalance of BCAAs in the diet. So, a low crude protein diet must supplement with Val in a range of 0.01–0.20 % for optimal growth performance. The present review reflects on the studies undertaken to assess the effect of dietary levels of Val on growth performance, immunity, gut health, carcass traits, and bone mineralization in broilers. Several studies have revealed that supplementation of valine in higher levels than the present recommendation of NRC (0.72–0.73% in the finisher phase), improves weight gain, feed: gain ratio, intestinal morphology, carcass characteristics, immune response, and increased bone density and strength. According to the data from the literature discussed in this survey, the Val to-lysine ratio recommendation might require reaching 0.86 for high-yielding broilers from 0-15 days of age. It also suggests that the ratio of digestible valine to lysine is between 75 and 84% in growing and finishing. For best feed intake, weight gain, and FCR, studies indicate that 0.903% is the recommended digestible Val level for a better overall performance of 22 to 42 d broilers. This review provides a summary of the addition of valine to the broiler diet and its potential influence on productive performance, immunity, gut health, carcass characteristics, and bone mineralization in birds.
Keywords: Growth Performance; L-valine; Broilers; Carcass Traits; Bowel Health